Types and formation mechanisms of diagenetic fractures in shale - Yue Zeng; Miao Shi; Jinchuan Zhang; Zhongming Li; Jialiang Niu; Tianshu Yuan; Yuchao Ma; Menglian Sun; Lixun Bai (Sedimentary Geology, 2026)

How additives steer sewage sludge hydrochar properties: Divergent pathways of MgO/CaO versus sawdust in carbon/nutrient fate and magnetism - Chen Zhang; Guo Chen; Qinghai Wang; Huafen Li; Yanan Wan; Guoxin Sun; Ke Wang; Tianshu Chu; Ruilun Zheng (Bioresource Technology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Source, transport and impact of biomass burning emissions in spring 2024 in Yunnan, China - Lihui Lv; Feng Xiang; Haitao Xie; Fei Qiu; Ying Pan; Zihuai Yi; Zenan Wang; Zhichao Liu; Limei Bi; Lu Zhao; Qianqian Sun; Shuai Wang; et al. (Journal of Environmental Sciences, 2026)

Toward sustainable lithium recovery from brine: a hydrothermal carbon-coating strategy for minimizing Mn dissolution in ion-sieve adsorbents - Tianshu Bao; Congcong Li; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Lili Yu; Xinjuan Hou; Aiping Peng; Ming Ye (Resources, Conservation and Recycling, 2026)

Corrigendum to “maternal smoking during pregnancy could accelerate biological aging in the adulthood: Evidence from a perspective study in UK biobank.” [Sci. Total Environ., 951(2014) 175150] - Wenbo Jiang; Xinyi Sun; Conghui Qiao; Xinyu Shan; Yiwei Tang; Yingdong Zuo; Xinyang Wang; Tianshu Han; Wei Wei (Science of The Total Environment, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Change of chemical compositions of the regional free troposphere in North China during COVID-19: Observational evidence from the Mt. Tai observatory - Yue Sun; Yujiao Zhu; Can Dong; Yingnan Zhang; Yujian Bi; Di Wu; Xiangkun Yin; Hengqing Shen; Tianshu Chen; Hongyong Li; Yuqiang Zhang; Qinyi Li; et al. (Atmospheric Environment, 2026)

Nicotinamide metabolic dysregulation plays a key role in Benzo[a]pyrene-induced adverse birth outcomes: Evidence from multi-omics profiling, experimental and epidemiological validation - Nan Zhao; Wei Song; Tianshu Sun; Weiwei Wu; Yongliang Feng; Ning Ma; Suping Wang (Journal of Hazardous Materials, 2025)

Breeding for yield improvements increases soybean seed N uptake due to enhanced N fixation under soil compaction - Tianshu Wang; Li Wang; Huajun Sun; Shuihong Yao; Yili Meng; Dawei Guan; Xinhua Peng; Bin Zhang (Plant and Soil, 2025)

Codon Usage Pattern of Papillomavirus E6, E7, and L1 Genes Across Hosts - Xudong Liu; Kexin Li; Xiaojing Chen; Yaqian Li; Tianshu Sun; Roujie Huang; Yanan Shi; Zilong He; Lei Li (Current Microbiology, 2025)

Design, synthesis, and application of negative ion-ion sieve synergistic adsorbent based on cross-linked carrier - Tianshu Bao; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Yong Wang; Xinjuan Hou; Aiping Peng; Ming Ye (Desalination, 2025)

Current perspectives on debt-for-nature swaps: moving from exploratory to empirical research - Christoph Nedopil; Tianshu Sun (Current Opinion in Environmental Sustainability, 2025)

Study on the characteristics of precipitation particle size distribution during freezing weather in the southwest mountainous areas of China - Haopeng Wu; Shengjie Niu; Seong Soo Yum; Jingjing Lü; Chunsong Lu; Yue Zhou; Jing Sun; Yixiao He; Tianshu Wang; Xinyi Wang (Science China Earth Sciences, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Similarity of Chinese and Pakistani oral microbiome - Xiaofang Sun; Binghua Han; Qian Han; Qiaoling Yu; Sijie Wang; Jie Feng; Tianshu Feng; Xiaoshan Li; Shiheng Zhang; Huan Li (Antonie van Leeuwenhoek, 2024)

Maternal smoking during pregnancy could accelerate aging in the adulthood: evidence from a perspective study in UK Biobank - Wenbo Jiang; Qianqian Lei; Wei Gao; Xinyi Sun; Conghui Qiao; Xinyu Shan; Yiwei Tang; Yingdong Zuo; Xinyang Wang; Tianshu Han; Wei Wei; Dandan Zhang (Science of The Total Environment, 2024)

Efficacy and safety of transvaginal mesh repair in a cohort with a minimum of 10-year follow-up - Zhibo Zhang; Jianbin Guo; Weijie Tian; Ye Zhang; Yuelun Zhang; Tianshu Sun; Jiali Duan; Xinmiao Bao; Yuan Wang; Yang Ye; Qianqian Gao; Honghui Shi; et al. (Science China Life Sciences, 2024)

Process intensification of tar chemical looping reforming based on ReaxFF reaction kinetics investigation - Zhe Li; Tianshu Wang; Yang Sun; Zhe Cui; Bin Liu; Wende Tian (Journal of Cleaner Production, 2024)

The association between blue light exposure and incidence of type 2 diabetes: A prospective study of UK biobank - Cheng Wang; Yang Zhao; Qianqi Hong; Yating Lei; Shengyuan Wang; Weiqi Wang; Wei Wei; Changhao Sun; Tianshu Han (Environmental Research, 2024)

Soil compaction development facilitated the decadal improvement of the root system architecture and rhizosheath soil traits of soybean in the North China Plain - Li Wang; Tianshu Wang; Shuihong Yao; Huajun Sun; Bin Zhang (Soil and Tillage Research, 2024)

Hazard or Non-Hazard Flood: Post Analysis for Paddy Rice, Wetland, and Other Potential Non-Hazard Flood Extraction from the VIIRS Flood Products - Donglian Sun; Tianshu Yang; Sanmei Li; Mitchell Goldberg; Satya Kalluri; Sean Helfrich; Bill Sjonberg; Lihang Zhou; Qingyuan Zhang; William Straka; Ruixin Yang; Fernando Miralles-Wilhelm (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Engineering hydroxyls on a metal-organic framework as Adsorbers and high-activity Dehydrochlorination sites for selective gold recovery - Tianshu Zhang; Zhiang Hou; Xiaoqiang An; Meng Sun; Huachun Lan; Huijuan Liu; Jiuhui Qu (Resources, Conservation and Recycling, 2023)

The efficiency evaluation and the spatiotemporal differences of CO2 emissions in China's construction industry - Ken Sun; Jingmin Han; Weidong Sun; Tianshu Yan; Chang Liu; Zhenzhen Yang; Wenbo He; Weisheng Xie (Journal of Cleaner Production, 2023)

Ultrafast and facile construction of programmable, multidimensional wrinkled-patterned polyacrylamide/sodium alginate hydrogels for human skin-like tactile perception - Jianhua Huang; Gong Chen; Tianhang Han; Chenxin Yi; Yujia Zhang; Lang Ding; Tianshu Sun; Ting Jin; Shuai Zhou (Carbohydrate Polymers, 2023)

Improving photosynthetic efficiency toward food security: Strategies, advances, and perspectives - Edward N. Smith; Marvin van Aalst; Tiina Tosens; Ülo Niinemets; Benjamin Stich; Tomas Morosinotto; Alessandro Alboresi; Tobias J. Erb; Paul A. Gómez-Coronado; Dimitri Tolleter; Giovanni Finazzi; Gilles Curien; et al. (Molecular Plant, 2023)

One-step in situ construction of anisotropic bilayer hydrogel with high sensitivity and wide detection range for adaptive tactile sensing - Lujing Wang; Yangrong Peng; Jingtong Liu; Chenxin Yi; Tianhang Han; Lang Ding; Zhenyang Luo; Tianshu Sun; Shuai Zhou (Chemical Engineering Journal, 2023)

Dysregulation of the microbiota-brain axis during long-term exposure to polystyrene nanoplastics in rats and the protective role of dihydrocaffeic acid - Wenbo Jiang; Cong Hu; Yunyan Chen; Yue Li; Xinyi Sun; Huanyu Wu; Ruiming Yang; Yiwei Tang; Fengru Niu; Wei Wei; Changhao Sun; Tianshu Han (Science of The Total Environment, 2023)

Ecological security evaluation and early warning in the water source area of the Middle Route of South-to-North Water Diversion Project - Ken Sun; Wenbo He; Yufang Shen; Tianshu Yan; Chang Liu; Zhenzhen Yang; Jingmin Han; Weisheng Xie (Science of The Total Environment, 2023)

Two-year online measurements of volatile organic compounds (VOCs) at four sites in a Chinese city: Significant impact of petrochemical industry - Jiangshan Mu; Yingnan Zhang; Zhiyong Xia; Guolan Fan; Min Zhao; Xiaoyan Sun; Yuhong Liu; Tianshu Chen; Hengqing Shen; Zhanchao Zhang; Huaicheng Zhang; Guang Pan; et al. (Science of The Total Environment, 2023)

Investigation on the vertical distribution and transportation of PM2.5 in the Beijing-Tianjin-Hebei region based on stereoscopic observation network - Tingting Sun; Tianshu Zhang; Yan Xiang; Guangqiang Fan; Yibin Fu; Lihui Lv (Atmospheric Environment, 2023)

Advances in coastal ocean boundary layer detection technology and equipment in China - Haitao Zheng; Youwen Sun; Tao Luo; Xueling Cheng; Shiyong Shao; Shouyin Zheng; Bangyi Tao; Bin Chen; Qianguang Tu; Kan Huang; Bingbing Wang; Mian Wang; et al. (Journal of Environmental Sciences, 2023)

Impact assessment on the economy, society, resource, and environment in the water-receiving cities of the Middle Route Project of South-to-North Water Diversion - Ken Sun; Yufeng Hua; Wenbo He; Tianshu Yan; Chang Liu (Environmental Science and Pollution Research, 2022)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Dichloroacetic acid-induced dysfunction in rat hippocampus and the protective effect of curcumin - Wei Wei; Qiuying Dong; Wenbo Jiang; Yue Wang; Yingying Chen; Tianshu Han; Changhao Sun (Metabolic Brain Disease, 2021)

Study on Enhanced Dissolution of Azilsartan-Loaded Solid Dispersion, Prepared by Combining Wet Milling and Spray-Drying Technologies - Tianshu Lu; Yinghua Sun; Dawei Ding; Qi Zhang; Rui Fan; Zhonggui He; Jing Wang (AAPS PharmSciTech, 2017)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)